Tell Me Who You Vote for, and I'll Tell You Who You Are? The Associations of Political Orientation With Personality and Prosocial Behavior and the Plausibility of Evolutionary Approaches - Grünhage, Thomas; Reuter, Martin (Frontiers in Psychology, 2021)
Blatantly observable in the U.S. currently, the political chasm grows, representing a prototype of political polarization in most if not all western democratic political systems. Differential political psychology strives to trace back increasingly polarized political convictions to differences on the individual level. Recent evolutionary informed approaches suggest that interindividual differences in political orientation reflect differences in cooperativeness and group-mindedness. Contrarily, the existence of meaningful associations between political orientation, personality traits, and interpersonal behavior has been questioned critically. Here, we shortly review evidence showing that these relationships do exist, which supports the assumption that political orientation is deeply rooted in in the human condition. Potential reasons for the premature rejection of these relationships and directions for future research are outlined.